Aplicación del aceite esencial de cinnamomum zeylanicum (canela) como alternativa en la conservación química de alimentos - Cordova Llive, Kerly Alexandra (Machala : Universidad Técnica de Machala, 2022)
The application of the essential oil of Cinnamomum zeylanicum (Cinnamon) is proposed as an alternative in the chemical preservation of food. The food industry, in the need to offer products with high quality and nutritional standards, makes use of traditional synthetic agents, the same ones that lead to negative reactions that arise in human health. Objective: Analyze the application of the essential oil of Cinnamomum zeylanicum, through a bibliographic review of scientific articles for its use as an alternative to chemical preservatives for the safe consumption of food products. Methodology: it is suggested to obtain the essential oil by means of the technique of hydrodistillation assisted with microwaves, later the identification of the chemical compounds that contains the essential oil of cinnamon by gas chromatography coupled to mass spectrophotometry, the parameters for the quality control of the product are also presented, essential oil of the plant material under study, the Kirby-Bauer method is also proposed in different concentrations of the oil to know the minimum inhibitory concentration and minimum bactericidal concentration. Conclusion: The application of the essential oil of Cinnamomum zeylanicum is shown to be a natural alternative to preserve food, obtaining positive results in concentrations of the essential oil of cinnamon.
Se propone la aplicación del aceite esencial de Cinnamomum zeylanicum (Canela), como alternativa en la conservación química de alimentos. La industria alimentaria en la necesidad de ofrecer productos con altos estándares de calidad y nutricionales, hace uso de agentes sintéticos tradicionales, los mismos que conllevan reacciones negativas que afectan la salud humana. Objetivo: Analizar la aplicación del aceite esencial de Cinnamomum zeylanicum, mediante una revisión bibliográfica de artículos científicos para su uso como alternativa ante conservadores químicos para el consumo seguro de productos alimenticios. Metodología: se sugiere obtener el aceite esencial mediante la técnica de hidrodestilación asistida con microondas, posteriormente la identificación de los compuestos químicos que contiene el aceite esencial de canela por cromatografía de gases acoplada a espectrofotometría de masas, también se presentan los parámetros para el control de calidad del aceite esencial de la materia vegetal en estudio, asimismo se propone el método Kirby-Bauer en diferentes concentraciones del aceite para conocer la concentración mínima inhibitoria y concentración mínima bactericida. Conclusión: El empleo del aceite esencial de Cinnamomum zeylanicum se demuestra que podría ser una alternativa natural para conservar alimentos obteniendo resultados positivos en concentraciones del aceite esencial de canela.
Keywords: CINNAMOMUM ZEYLANICUM; ACEITE ESENCIAL; ALDEHIDO CINAMICO; CONSERVANTE